Estimating molecular preservation of the intestinal microbiome via metagenomic analyses of latrine sediments from two medieval cities. (23rd November 2020) - Sabin, Susanna; Yeh, Hui-Yuan; Pluskowski, Aleks; Clamer, Christa; Mitchell, Piers D.; Bos, Kirsten I.
Abstract : Ancient latrine sediments, which contain the concentrated collective biological waste of past whole human communities, have the potential to be excellent proxies for human gastrointestinal health on the population level. A rich body of literature explores their use to detect the presence of gut-associated eukaryotic parasites through microscopy, immunoassays and genetics. Despite this interest, a lack of studies have explored the whole genetic content of ancient latrine sediments through consideration not only of gut-associated parasites, but also of core community gut microbiome signals that remain from the group that used the latrine. Here, we present a metagenomic analysis of bulk sediment from medieval latrines in Riga (Latvia) and Jerusalem. Our analyses reveal survival of microbial DNA representative of intestinal flora as well as numerous parasites. These data are compared against parasite taxon identifications obtained via microscopy and ELISA techniques. Together, these findings provide a first glimpse into the rich prokaryotic and eukaryotic intestinal flora of pre-industrial agricultural populations, which may give a better context for interpreting the health of modern microbiomes. This article is part of the theme issue 'Insights into health and disease from ancient biomolecules'.